The Impact of Peer Effects on Teachers' Teaching Ability Enhancement in the Context of "Promoting Teaching Through Competition" (Journal of educational development exploration, 2025)
Against the backdrop of "promoting teaching through competitions," this paper explores the influence mechanism of peer effects on the enhancement of college teachers' teaching abilities. Based on social cognitive theory and social comparison theory, the study constructs a theoretical model incorporating cooperative peer effects, competitive peer effects, and self-efficacy, aiming to reveal how these two types of peer effects influence teachers' teaching abilities through the mediating role of self-efficacy. A questionnaire survey was conducted to collect 377 valid responses, and structural equation modeling was employed for data analysis. The results show that both cooperative and competitive peer effects significantly enhance teachers' self-efficacy and teaching abilities. Furthermore, self-efficacy plays a significant partial mediating role between both types of peer effects and teaching abilities, validating the "environment-cognition-ability" pathway. The study provides theoretical and practical foundations for optimizing competition designs and advancing teacher professional development, emphasizing the need to balance collaboration and competition in the process of "promoting teaching through competitions" and highlighting the cultivation of teachers' self-efficacy to achieve comprehensive improvement in teaching capabilities.
Keywords: Teaching ability; Peer effects; Promoting teaching through competition; Structural equation model (SEM); Self-efficacy